2021
DOI: 10.1007/s13353-021-00656-x
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome of Secale sylvestre (Poaceae: Triticeae)

Abstract: Secale sylvestre is a wild species of rye, morphologically distinct from domestic species. To draw comparisons between species based on molecular features, it is important to have high-quality sequences, especially in the case of organellar genomes. For such reason, the complete chloroplast genome of Secale sylvestre Host introd. no. 6047 will provide useful data for ecological, agricultural, and phylogenetic purposes. Here we present the complete, annotated chloroplast genome sequence of Secale sylvestre Host… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…segetale cp genome appeared as a typical circular, double-stranded molecule (Fig. 1 ) and overal GC content, which is similar to previously sequenced plastomes of S. cereale (137,051 bp; NCBI LC645358), S. sylvestre (137 116 bp) 10 or within the size range of angiosperms 20 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…segetale cp genome appeared as a typical circular, double-stranded molecule (Fig. 1 ) and overal GC content, which is similar to previously sequenced plastomes of S. cereale (137,051 bp; NCBI LC645358), S. sylvestre (137 116 bp) 10 or within the size range of angiosperms 20 .…”
Section: Discussionsupporting
confidence: 81%
“…The chloroplast genome of S. segetale has recently been published 11 , however a comprehensive phylogenetic analysis based on whole chloroplast genomes has not been done to date. Therefore, we presume that analysis of the complete chloroplast genome sequences of Secale spp., starting with S. sylvestre 10 , will be useful and cost-effective for evolutionary and phylogenetic studies, as it was suggested by our previous studies 12 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In particular, for its exhibiting variations at the intra-species level, the genome has been widely used for the study of systematics and evolution among different populations [ 25 , 26 ]. In recent years, more and more complete chloroplast genomes in plants have been reported [ 27 , 28 , 29 ], which provide more valuable information and screen more new markers with potentially high resolution for more comprehensive research in the future to better resolve the phylogenetic relationships and intraspecific diversity of the Rhus species. At present, there were three complete chloroplast genomes of R. chinensis reported [ 21 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we found that these three genomes showed large differences in both sequence length, from 149,011 bp to 158,809 bp, and number of genes, from 126 to 130, which is very unusual for different accessions of the same species. Hence, it is important to obtain the high-quality genome sequences, especially in the case of organellar genomes, for the analysis of genetic diversity and phylogenetics [ 29 ].…”
Section: Introductionmentioning
confidence: 99%